2021
DOI: 10.3389/fphar.2021.638209
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Angiogenesis Effects of Levetiracetam Following Ischemic Stroke in Rats

Abstract: Objective: The present study explored whether levetiracetam (LEV) could protect against experimental brain ischemia and enhance angiogenesis in rats, and investigated the potential mechanisms in vivo and in vitro.Methods: The middle cerebral artery was occluded for 60 min to induce middle cerebral artery occlusion (MCAO). The Morris water maze was used to measure cognitive ability. The rotation test was used to assess locomotor function. T2-weighted MRI was used to assess infarct volume. The neuronal cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…Three tests were performed on the 1st, 7th and 14th after MCAO. The best score on that day was recorded [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three tests were performed on the 1st, 7th and 14th after MCAO. The best score on that day was recorded [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…BSCB plays a critical role in protecting the spinal cord away from macrophage-mediated inflammatory stress, and BSCB disruption can promote the deterioration of SCI. Levetiracetam has been proved to improve the ischemic reperfusion injury of cerebral nerve cells [ 15 , 16 ]. However, few studies have revealed the function of levetiracetam in the acute trauma of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Nootropics are not supposed to reduce the volume of the stroke lesion. Leviterocetam improves the cognitive functions of rats in the MCAO model by enhancing angiogenesis and reducing the inflammatory process [ 38 ]. Microglial activation can persist for a long time in the post-stroke state and impair the recovery of mnestic functions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%